Comparative Genomic Analysis of the Hydrocarbon-Oxidizing Dibenzothiophene-Desulfurizing Gordonia Strains - Ekaterina Frantsuzova; Yanina Delegan; Alexander Bogun; Diyana Sokolova; Tamara Nazina (Microorganisms, 2022)
A number of actinobacteria of the genus Gordonia are able to use dibenzothiophene (DBT) and its derivatives as the only source of sulfur, which makes them promising agents for the process of oil biodesulfurization. Actinobacteria assimilate sulfur from condensed thiophenes without breaking the carbon–carbon bonds, using the 4S pathway encoded by the dszABC operon-like structure. The genome of the new dibenzothiophene-degrading hydrocarbon-oxidizing bacterial strain Gordonia amicalis 6-1 was completely sequenced and the genes potentially involved in the pathways of DBT desulfurization, oxidation of alkanes and aromatic compounds, as well as in the osmoprotectant metabolism in strain 6-1 and other members of the genus Gordonia, were analyzed. The genome of G. amicalis strain 6-1 consists of a 5,105,798-bp circular chromosome (67.3% GC content) and an 86,621-bp circular plasmid, pCP86 (65.4% GC content). This paper presents a comparative bioinformatic analysis of complete genomes of strain 6-1 and dibenzothiophene-degrading Gordonia strains 1D and 135 that do not have the dsz operon. The assumption is made about the participation in this process of the region containing the sfnB gene. Genomic analysis supported the results of phenomenological studies of Gordonia strains and the possibility of their application in the bioremediation of oil-contaminated environments and in the purification of oil equipment from oil and asphalt-resin-paraffin deposits.